Unravelling single cell genomics : micro and nanotools - Bontoux, Nathalie; Dauphinot, Luce; Potier, Marie-Claude; Royal Society of Chemistry (Great Britain) (Cambridge, UK : Royal Society of Chemistry, 2010)
PSZJBL